The NASSS Framework - a synthesis of multiple theories of technology implementation - Greenhalgh, T; Abimbola, S (IOS Press, 2019)
Technologies are often viewed as the route to better, safer and more efficient care, but technology projects rarely deliver all the benefits expected of them. Based on a literature review and empirical case studies, we developed a framework (NASSS) for studying the non-adoption, abandonment and challenges to scale-up, spread and sustainability of technology-supported change efforts in health and social care. Such projects meet problems usually because they are too complex - and because the complexity is sub-optimally handled. NASSS consists of six domains - the illness or condition, the technology, the value proposition, the individuals intended to adopt the technology, the organisation(s) and the wider system - along with a seventh domain that considers how all these evolve over time. The NASSS framework incorporates a number of other theories and analytic approaches described elsewhere in this book. It is not intended to offer a predictive or formulaic solution to technology adoption. Rather, NASSS should be used to generate a rich and situated narrative of the multiple influences on a complex project; to identify parts of the project where complexity might be reduced; and to consider how individuals and organisations might be supported to handle the remaining complexities better.